Hepatoprotective Activity of Thalictrum Foliolosum (Ranunculaceae) Root Ethanolic Extract: Pharmaceutical Science-Pharmacology for drug discovery - Gregory Marslin; Jose Prakash (International Journal of Life Science and Pharma Research, 2022)
The trend in healthcare is moving towards disease prevention rather than treatment, wherein people choose herbal medicines, functional foods and nutraceuticals over pharmaceuticals for their wellbeing. Thalictrum foliolosum is one of the well- known medicinal plants used in Indian traditional medicine to treat several disease, studies related to the pharmacological properties of Thalictrum foliolosum are very less. The Thalictrum foliolosum root is widely used as traditional medicine to treat various diseases including antiperiodic, diuretic, febrifuge, ophthalmic diseases. In this present investigation we studied the hepatoprotective activity of T. foliolosum root ethanolic extract for the first time. Dried roots of T.foliolosum were, powdered and extracted in ethanol. A single oral doses of Thalictrum foliolosum root ethanolic extract (250, 500 and 1000 mg/kg) was used for acute toxicity study. The acute-toxicity studies show that the extract is non-toxic even at relatively higher concentrations (1000 mg/kg). Wister rats were administered with silymarin or T. foliolosum root ethanolic extract for one week. On the fifth day except the control group, all the test animals were administered with 2 g/kg paracetamol to induce hepatotoxicity. The biochemical parameters and histopathological parameters were used to measure hepatoprotective activity of T.foliolosum root ethanolic extract. Behavioral observation, biochemical analysis of serum and histopathological examination of the experimental animals indicated that T. foliolosum root ethanolic extract offer significantly higher hepatoprotection.